1987
DOI: 10.2527/jas1987.6551243x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neomycin, Carbadox and Length of Adaptation to Calorimeter on Performance, Fasting Metabolism and Gastrointestinal Tract of Young Pigs1

Abstract: Five sets of littermate gilts (8.2 +/- .19 kg average initial weight) were randomly assigned within litter to a 16% protein corn-soybean meal basal diet (B), B + .308% neomycin, or B + 55 ppm carbadox. Each set was equally-fed individually once daily for 16 d in metabolism cages and 5 d in calorimeters. The average daily feed intake for 21 d was 276 g. Oxygen consumption and CO2 production were measured during an 8- to 24-h postprandial period on d 16, 19, 20 and 21, and during a 32- to 48-h postprandial perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, they reported that antibacterial agents, used as growth promoters, are able to reduce the intestinal microflora, which competes with the host for nutrients in the intestinal lumen. They also found that a significant reduction of bacterial density on the intestinal epithelium by antibacterial growth promoters, contributed to a more efficient absorption of nutrients by the animal CARB improves weight gain and efficiency of feed utilization, and reduces the mass of small intestine in young pigs [11][12]. Portal vein-drained organs (PVDO), which consist of gastrointestinal tract, spleen, and pancreas, were shown to play an important role in the oxidative demand of the pig because they used 25% of the O 2 consumed by the whole animal, although PVDO represented only 5% of the wholebody weight [13].…”
Section: Growth-promoting Properties and Toxicity Of Quinoxaline 14-mentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, they reported that antibacterial agents, used as growth promoters, are able to reduce the intestinal microflora, which competes with the host for nutrients in the intestinal lumen. They also found that a significant reduction of bacterial density on the intestinal epithelium by antibacterial growth promoters, contributed to a more efficient absorption of nutrients by the animal CARB improves weight gain and efficiency of feed utilization, and reduces the mass of small intestine in young pigs [11][12]. Portal vein-drained organs (PVDO), which consist of gastrointestinal tract, spleen, and pancreas, were shown to play an important role in the oxidative demand of the pig because they used 25% of the O 2 consumed by the whole animal, although PVDO represented only 5% of the wholebody weight [13].…”
Section: Growth-promoting Properties and Toxicity Of Quinoxaline 14-mentioning
confidence: 95%
“…For example, 2-methyl-3-phenylquinoxaline (12), when treated with peroxide and acetic acid, yields a mixture of the 1,4-dioxide (13) and the 1-oxide (14) derivatives [154] of Fig. (20).…”
Section: ) Cyclization and Cycloaddition Reactionsmentioning
confidence: 99%